Multispecialty Interprofessional Team Memory Clinics: Enhancing Collaborative Practice and Health Care Providers' Experience of Dementia Care. Issue 1 (30th March 2022) - Lee, Linda; Molnar, Frank; Hillier, Loretta M.; Patel, Tejal; Slonim, Karen
Abstract: This study explored whether working within Multispecialty INterprofessional Team (MINT) memory clinics has an impact on health care professionals' perceptions of the challenges, attitudes, and level of collaboration associated with providing dementia care. Surveys were completed by MINT memory clinic members pre- and 6-months post-clinic launch. A total of 228 pre-and-post-training surveys were matched for analysis. After working in the MINT memory clinics for 6 months, there were significant reductions in mean ratings of the level of challenge associated with various aspects of dementia care, and significant increases in the frequency with which respondents experienced enthusiasm, inspiration, and pride in their work in dementia care and in ratings of the extent of collaboration for dementia care. This study provides some insights into the effect of collaborative, interprofessional approaches on health care professionals' perceptions of the challenges and attitudes associated with providing dementia care and level of collaboration with other health professionals.